METHODOLOGICAL FOUNDATIONS OF RESEARCH ON WOMEN’S ISSUES IN MODERN SOCIETIES - Shodieva Zebiniso Nurmamadovna (Zeta Repository, 2023)
In this article, the author theoretically analyzed the methodological foundations of research on women’s issues in modern societies. The role of women in society and the scientific definitions given to them were intended to provide theoretical explanations based on their point of view.